Vitamin D Levels in Patients With Small and Medium Vessel Vasculitis [Niveles de vitamina D en pacientes con vasculitis de pequeños y vasos medianos] - AŞICIOĞLU, EBRU; DİRESKENELİ, RAFİ HANER; TUĞLULAR, ZÜBEYDE SERHAN (Ediciones Doyma, S.L., 2021)
Objectives: To determine the prevalence of vitamin D deficiency in patients with small and medium vessel systemic vasculitis. Methods: In this cross-sectional study, 25-hydroxy (OH) vitamin D3 levels were measured in adult patients with systemic small and medium vessel vasculitis including antineutrophil cytoplasmic antibody-associated vasculitis (AAV), cryoglobulinaemic vasculitis (CryV), IgA vasculitis (IgAV) and polyarteritis nodosa (PAN), and age- and sex-matched healthy subjects (HS) and patients with rheumatoid arthritis (RA) as control groups. 25OH vitamin D3 levels < 30 ng/ml and <20 ng/ml were regarded as insufficiency and deficiency, respectively. Results: Fifty-seven patients (42 AAV, 2 CryV, 8 IgA vasculitis, 5 PAN) with systemic vasculitis, 101 HS, and 111 RA patients were included. The mean 25OH vitamin D3 level was 21.8 ± 14.2 ng/mL in patients with vasculitis, 42.7 ± 27.6 ng/mL in HS (p < .001) and 20.1 ± 18.47 ng/mL in patients with RA (p = .54). Vitamin D insufficiency and deficiency were significantly higher in patients with systemic vasculitis compared to HS (75.4% vs 33.7%, p < .001; %50 vs 21.8%, p < .001, respectively). Vitamin D status was not different in patients with systemic vasculitis compared to RA. There was a negative correlation between vitamin D status and CRP levels (=−.364, p = .007). The multivariate logistic regression analysis showed that renal involvement was significantly associated with vitamin D deficiency/insufficiency in patients with vasculitis (OR 22.5 [95% CI 1.6–128.9]. Conclusion: Vitamin D deficiency and insufficiency are more frequent in patients with systemic small and medium vessel vasculitis and RA than HS. Renal involvement is one of the factors associated with vitamin D deficiency/insufficiency in patients with vasculitis. © 2020 Elsevier España, S.L.U. and Sociedad Española de Reumatología y Colegio Mexicano de Reumatología
Keywords: Deficiency; Rheumatoid arthritis; Vasculitis; Vitamin D